Socio-hydrological Analysis Protocol Adaptation to NW São Paulo State, Brazil - Borges, Adriana Sanches [UNESP]; Manzione, Rodrigo Lilla [UNESP]; Re, Viviana (Springer Nature, 2021)
Groundwater is an economically viable resource for the supply of agricultural, industrial, public and small rural areas. However, there is a lack of knowledge about groundwater quantity and quality issues, being a passive resource for depletion and pollution. Given that the agricultural sector is one of the largest consumers of water and that it is an essential and strategic component of food security, proper control and administration enables balanced use management. At present, effective procedures for bringing water users and technicians closer together are not structured to ensure the application of practices that lead to sustainable groundwater use in agriculture. Therefore, this work aimed to create ways to bring farmers and rural communities closer to the theme of groundwater, to ensure its preservation and good use, by using socio-hydrogeology approaches. These approaches targeted to bridge the gap between technicians and water users by disseminating information and discussions on groundwater management, and this work intends to develop and implement a groundwater communication protocol in rural communities based on previous studies. Modification and adaptations of the analysis protocol are proposed to the northwester part of São Paulo State, Brazil.
Keywords: Rural communities; Socio-hydrology; Water users